2020
DOI: 10.1021/acs.organomet.0c00046
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of PdII Complexes Bearing pNHC Ligands by Oxidative Addition of 8-Halogenotheophyllines and 8-Bromoadenine to Pd0

Abstract: Various 8-halogenotheophyllines (halogen = Cl, Br, I) were selectively C8 metalated by an oxidative addition of the C8–halogen bond to [Pd­(PPh3)4] to give the PdII azolato complexes [1]–[3]. The complexes were protonated at the N9 nitrogen atom to yield the NH,NH-NHC (pNHC) complexes [4]­BF4–[6]­BF4. Due to the unsymmetrical nature of the backbone of the theophylline-derived pNHC ligands, two NH resonances were observed by 1H NMR spectroscopy. In addition, 8-bromoadenine was also regioselectively C8 metalated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Comparing its structure with that of [(IMes)­Co­(η 2 :η 2 -dvtms)] revealed that the reduction reaction has resulted in the conversion of the IMes ligand into a N -mesityl imidazolate ligand with K­(18-crown-6) coordinating on the N 3 position. Similar imidazolate complexes without a cation coordinated by the unsubstituted ring nitrogen atom have been obtained by the oxidative addition of neutral 2-halogenoazoles to suitable (low-valent) transition-metal complexes. The K–N distance (2.727(3) Å) is typical of the ionic K–N bond of potassium N -imidazolate compounds . The N -mesityl imidazolate ligand has C1–N1 and C1–N2 distances of 1.348(3) and 1.388(4) Å, respectively, and C1–N1–C6 and C1–N2–C7 angles of 110.0(2)°.…”
Section: Results and Discussionsupporting
confidence: 74%
“…Comparing its structure with that of [(IMes)­Co­(η 2 :η 2 -dvtms)] revealed that the reduction reaction has resulted in the conversion of the IMes ligand into a N -mesityl imidazolate ligand with K­(18-crown-6) coordinating on the N 3 position. Similar imidazolate complexes without a cation coordinated by the unsubstituted ring nitrogen atom have been obtained by the oxidative addition of neutral 2-halogenoazoles to suitable (low-valent) transition-metal complexes. The K–N distance (2.727(3) Å) is typical of the ionic K–N bond of potassium N -imidazolate compounds . The N -mesityl imidazolate ligand has C1–N1 and C1–N2 distances of 1.348(3) and 1.388(4) Å, respectively, and C1–N1–C6 and C1–N2–C7 angles of 110.0(2)°.…”
Section: Results and Discussionsupporting
confidence: 74%
“…Complexes [ 1 ]–[ 4 ] constitute additional examples for the preferred oxidative addition of 8-halogenotheophyllines to transition metals proceeding under the reaction of the N7–H bond while the C8–halogen bond remains intact. Previously, we reported the N7–H oxidative addition in the reaction of 8-halogenotheophyllines with [Ni­(cod) 2 ]/PEt 3 (Scheme , middle) and the C8–halogen oxidative addition in the same reaction with [Pd­(PPh 3 ) 4 ] (Scheme , bottom) . These reactions are most likely thermodynamically controlled .…”
Section: Resultsmentioning
confidence: 88%
“…Previously, we reported the N7–H oxidative addition in the reaction of 8-halogenotheophyllines with [Ni(cod) 2 ]/PEt 3 ( Scheme 1 , middle) 10 and the C8–halogen oxidative addition in the same reaction with [Pd(PPh 3 ) 4 ] ( Scheme 1 , bottom). 11 These reactions are most likely thermodynamically controlled. 10 The factors determining the outcome of the reaction of 8-halogenotheophyllines with Ir I complexes are not yet clear, but it appears that the formation of the N7^O1 chelate rings favors the N7–H oxidative addition over the reaction at the C8–X bond.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting diaminoheterocycles in [ 13a ] and [ 15a ] carry a negative charge at one of the ring nitrogen atoms. While these complexes have not been isolated, related azolato complexes have been observed multiple times. , The negatively charged ring nitrogen atom then attacked the C–F bond of a neighboring o -fluorophenyl group to give complexes [ 13b ] + and [ 15b ] + , respectively. This reaction is normally observed upon deprotonation of NH,NH-NHC ligands in the template-controlled preparation of [11]­ane-P 2 C NHC macrocycles (Scheme ).…”
Section: Resultsmentioning
confidence: 99%